2005
DOI: 10.1111/j.1600-6143.2004.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Caspase Inhibition Improves Ischemia-Reperfusion Injury After Lung Transplantation

Abstract: Ischemia-reperfusion injury is associated with cell death in many organ systems. The role of programmed cell death (PCD) pathways and the ultimate clinical relevance of PCD in the context of lung transplantation (LTx) are unknown.In randomized and blinded studies, rat single LTx was performed in the presence of caspase inhibitors after 'short' (6 h) and 'long' (18 h) periods of cold ischemic storage. Lung function, electron microscopic morphology, caspase 3, 8 and 9 activities and TUNEL assays were evaluated.E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…Neutrophils, in particular accelerate lung tissue damage by furthering the breakdown of the endothelial cell barrier through the production of a number of potent proteolytic enzymes and reactive oxygen species that directly lead to cell death (2). Loss of integrity of endothelial cell barrier leads to pulmonary edema and compromised blood oxygenation (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils, in particular accelerate lung tissue damage by furthering the breakdown of the endothelial cell barrier through the production of a number of potent proteolytic enzymes and reactive oxygen species that directly lead to cell death (2). Loss of integrity of endothelial cell barrier leads to pulmonary edema and compromised blood oxygenation (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…(29) Various studies have demonstrated that the inhibition of apoptosis by caspase inhibitors results in reduced lymphocyte infiltration and cell death, which leads to improved lung function. (6,30) In the present study, the assessment of apoptosis by the TUNEL method revealed no significant differences in the number of apoptotic cells between the 6-h period of ischemia and the 12-h period of ischemia in the LPD, HTK, or NS groups after 60 min of lung reperfusion. This finding can be interpreted in two different ways: first, the lack of differences might be due to severe ischemic injury, which was similar among the groups; second, the LPD and HTK solutions might be similar in terms of the quality of preservation (cell integrity).…”
Section: Discussionmentioning
confidence: 84%
“…Hypotension was more evident in the PPGI 2 group, a finding that is in agreement with those reported for models are not limited to vasodilation. (2) Prostanoids are also able to ameliorate reperfusion injury through direct cytoprotection, effected by mediating the balance between pro-and antiinflammatory cytokines. In rat models of lung transplantation, the administration of PGE 1 during reperfusion increases IL-10 in lung tissue, whereas it decreases TNF-α, IL-12, and IFN-γ.…”
Section: Discussionmentioning
confidence: 99%
“…Prostanoids have beneficial effects on graft function after reperfusion and are therefore added to intracellular solutions for preservation, such as the Euro-Collins and University of Wisconsin solutions. Because experimental animal studies have shown that prostaglandin E 1 (PGE 1 ) changes the cytokine profile from pro-inflammatory to antiinflammatory, (2) it has been incorporated into lung preservation protocols as an adjuvant to extracellular solutions. However, the addition of prostanoids directly to the pulmonary circulation causes severe systemic hypotension, and prolonged hypotension can cause lung graft dysfunction, which is why prostanoids can only be used immediately before lung extraction.…”
Section: Introductionmentioning
confidence: 99%